Stability in Time-Delay Systems: Quiet Standing Case Study - Fitri Yakub; Akira Kojima; Yasuchika Mori (Institute of Advanced Engineering and Science, 2013)
The analysis of linear time-delay systems has attracted much interest in the literature over last five decade. Two types of stability conditions, namely delay-independent which results guarantee stability for arbitrarily large delays and delay-dependent, results take into account the maximum delay that can be tolerated by the system and, thus, are more useful in applications. The stability in general for linear time-delay systems, can be checked exactly only by eigenvalue considerations. When reasonable chosen with intentional delays, case study effects on time-delay of ankle torque on the stability of quiet standing, it can be used to stabilize and improve the close-loop response of these systems.